Shaping the Future of Environmental Economics: A Bibliometric Review of Current Trends and Future Directions - Apriantoro, Muhamad Subhi; Rosadi, Rizki Dwi Putra; Ramdhani, Arminda Cahya; Andriyani, Ninik (International Journal of Energy Economics and Policy, 2024)
Environmental economics is increasingly pivotal in addressing global environmental challenges. This study aims to elucidate the research landscape in this field, focusing on prevalent themes such as climate change, carbon emissions, sustainable development, and environmental policy. Employing a bibliometric analysis, we analyzed a substantial corpus of literature from Scopus. We applied Lotka’s Law to assess author productivity and distribution and conducted institutional and country-level analyses to map the geographical spread and institutional affiliations in environmental economics research. Our analysis highlights a significant growth in the environmental economics literature, with a notable focus on climate change and sustainability. A concentration of publications among a few authors was observed, indicating influential researchers and potential for increased collaboration. The rise in publications, particularly in China and leading journals like ’The Journal of Cleaner Production,’ reflects a global upsurge in environmental economics research. Distinct clusters were identified, covering diverse topics from climate change economics to environmental policy. The study acknowledges limitations due to exclusive reliance on Scopus data, suggesting future research to include other databases like the Web of Science for a more comprehensive analysis. Considering the evolving nature of environmental challenges, we advocate for interdisciplinary approaches and continual updates in research to address emergent trends in this critical field.